When Images are not Enough: Text Adaptation of the US-based Image Memes into Indonesian Cultural Context - Sri Hariyatmi (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
This present study aims to examine the procedure of adaptation in four selected US-based image memes adapted to the Indonesian context. Four US-based image memes and their Indonesian adaptation were selected as the source of data. They were purposively chosen from some Indonesian memes’ websites and the US-based image memes. This study adopts Bastin’s theory of adaptation as the theoretical framework to analyze the adaptation procedure used by the Indonesian content creators in adapting the US-based image memes. The analysis of this descriptive qualitative study reveals that from the seven modes of Bastin’s adaption, the Indonesian content creators used the sixth procedure, situational or cultural adequacy for the adaptation of the US-based image memes to the Indonesian context.   This study concludes that the four selected US-based image memes under the present study have been localized by using Bahasa Indonesia to accommodate the cultural transfer that suits the Indonesian cultural settings. Secondly, Bahasa Indonesia used in the memes assigns a new cultural meaning that is socially understood by Indonesian memetic society. Lastly, this study is hoped to shed a light on the pedagogical field,  proposing that cultural awareness is significant in translation to bridge the cultural transfer from the source text to the new target readers.